The process of developing self‐report measures in intellectual disability: A case study of a complicated grief scale. (28th February 2019) - O'Keeffe, Lynsey; Guerin, Suzanne; McEvoy, John; Lockhart, Karen; Dodd, Philip
Accessible Summary: Developing ways of asking adults with intellectual disability about difficult topics such as death is important to our understanding. This study explores how adults with intellectual disabilities can be supported to report difficult experiences using the example of understanding death and bereavement. The paper describes the way in which we worked with adults with intellectual disabilities to understand how they preferred to talk about death and bereavement. This process showed us that it is possible to support adults with intellectual disabilities to talk about these difficult experiences. There are important lessons for researchers who want to talk with adults with intellectual disabilities about difficult topics and experiences. Abstract: Background: This paper considers the challenges regarding the development and use of self‐report tools for sensitive, personal topics, in this case experiences of death and bereavement for individuals with intellectual disabilities (ID). These challenges are represented through the experience of the development of a self‐report measure of complicated grief for use with individuals with intellectual disabilities. Materials and method: Focusing on the topic of bereavement, and using a case study format, this paper describes the development of a self‐report measure for complicated grief. Results: Following three phases of questionnaire development, the Complicated Grief Questionnaire for People with Intellectual Disabilities (CGQ‐ID) was adapted for use as a self‐report measure with individuals with intellectual disabilities. The development process, informed by recommendations in the research literature, provides evidence that self‐report is possible with individuals with intellectual disabilities even when the topic is as sensitive as bereavement and when abstract concepts such as emotions are involved. Conclusions: The adaptation process described here might provide a useful template for the development of other scales on sensitive topics.